2012
DOI: 10.12659/ajcr.883320
|View full text |Cite
|
Sign up to set email alerts
|

A near fatal case of invasive aspergillosis

Abstract: SummaryBackground:Invasive aspergillosis (IA) rarely presents with endobronchial nodules or pseudomembranes on bronchoscopy. We describe a case of invasive aspergillosis in a patient with systemic lupus erythematosus (SLE), in which a fungal etiology was suspected after visualization of scattered, white endobronchial nodules.Case Report:A 36-year-old-female with history of SLE developed cardiorespiratory shock. Bronchoscopy indicated the presence of endobronchial lesions, and serologic studies were consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Patients with IPA are often ill and may exhibit tachycardia, tachypnea and hypoxia [118]. Neutrophil counts can be low, normal or high depending on the underlying immune status and comorbidities of the host.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Patients with IPA are often ill and may exhibit tachycardia, tachypnea and hypoxia [118]. Neutrophil counts can be low, normal or high depending on the underlying immune status and comorbidities of the host.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Because of varying clinical manifestations, often of a severe nature-Aspergillosis remains a major cause of patient morbidity and is responsible for more than one million mortalities in immunocompromised populations worldwide, annually [ 4 ]. The central nervous system and cardiovascular system may be affected by the direct or hematogenous spread of Aspergillus fungal elements [ 5 - 7 ]. Aspergillosis of the ovary is extremely rare, only a few case studies are reported in the literature [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%